PENETRATION OF IMPORTED PRODUCTS ON E-COMMERCE PLATFORM IN INDONESIA AND STRATEGIES FOR IMPROVING LOCAL PRODUCT COMPETITIVENESS - Riesky Saputri Pratama Canover; Dwi Kartikasari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study discusses the penetration rate of imported products on e-commerce platform in Indonesia and strategies to improve local product competitiveness. The authors used the biggest e-commerce platform in three most sold product categories in 2019. Big data were collected from website on 126,366 clothing products, 504,118 beauty products, 1,966,046 electronics products, and 1,540 product reviews in the first quarter of 2020. The authors utilized qualitative analysis including descriptive analysis, sentiment analysis, content analysis, and SWOT analysis. This study found that the penetration rate of imported products on e-commerce platforms in Indonesia is high, at 66 percent for cosmetics, 58 percent for electronic accessories, and 40 percent for clothing. Positive reviews of local products are higher than those of imported products in all product categories where the aspects of quality and delivery are the most important things for customers when buying online. Some strategies to improve the competitiveness of local products against imported products, first, local producers and sellers should exploit the positive public sentiment towards local products against imported products. Second, the Indonesian government along with e-commerce platforms and education institutions should promote local producers and sellers to strengthen the later parties’ existence online. Third, the Indonesian government must enforce the law on e-commerce platforms. Fourth, the statistics bureau should collect e-commerce data. Last, local producers and sellers should be able to stage their product advantages against imported products comprising thoughtful service, fastest delivery, and standardized quality.